Urinary incontinence. - Santos, V V (1999)
After defining U.I. as a symptom, sign and condition, the author claims, through epidemiological studies, that this reflects a major medical, social and economic problem. On the other hand the physiopathology of U.I. can be explained in a context of balance between the retention and emptying forces during the filling phase. Therefore the author explains U.I. as an urgency due to overactive bladder as well as hypermobility of the bladder neck and/or injury of the intrinsic sphincter. The diagnosis and severity of the different types of U.I. are based on clinical history, the pad test, the diurnal fictional record and the Q tip test. The abnormal continence factors are measured by the following tests: plain XR of the urinary system, urinoculture, urodynamic studies, transvaginal ultrasound. The treatment of U.I. can be explained by the physiopathology and exemplified with clinical cases in a systematic way.